Revitalisasi Tari Mosau’ Bolaang Mongonow Melalui Penciptaan Tari Sinungkudan - Fahrurozy Ambaru Harun; Riana Diah Sitharesmi; Nurlia Djafar (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This research aimed to revitalize Mosau' Dance, a nearly extinct traditional dance from Bolaang Mongondow, through the creation of a new work entitled Sinungkudan Dance. Mosau' Dance is a celebratory dance of post-war warriors whose existence is currently fading in the Bolaang Mongondow region due to a lack of regeneration and the influence of modernization. This research employed a descriptive qualitative approach with a focus on choreographic analysis. The revitalization process was carried out through four stages: exploration, reconstruction, reinterpretation, and reactualization. The results indicate that revitalization through the creation of Sinungkudan Dance successfully provided a "new breath" for the local tradition of Bolaang Mongondow. Choreographically. Sinungkudan Dance consisted of eight movement variations, combining three original Mosau' movement motifs (such as joyful leaps) with five newly created movements that depicted narratives of warrior life (Bogani), ranging from weapon sharpening and physical training to the atmosphere of warfare. The choreographic structure was supported by nine symbolic floor patterns, the use of the tungkudon (spear) as a prop, and digital musical accompaniment that blended traditional rhythms with modern instruments such as the flute and snare drum. In conclusion, through more visually and kinetically attractive innovations, the values of leadership and resilience embodied in Mosau' Dance were able to be transmitted to younger generations as a proud cultural identity for the people of Bolaang Mongondow.